Comparative assessment of LiDAR and conventional methods in evaluating genetic parameters of eucalypt progeny trials - Jatzek, Vitor Augusto; Filho, Humberto Menecheli; Rocha, Guilherme Nichele; Silva, Otávio Jerônimo; Rodriguez, Luiz Carlos Estraviz; Paula, Rinaldo Cesar de [UNESP]; Silva, Paulo Henrique Müller da (My University, 2025)
This study compared Light Detection and Ranging (LiDAR) and conventional methods in progeny trials of Eucalyptus cloeziana and E. saligna. Two populations, derived from open-pollinated progenies, were evaluated by using a randomized complete block design. Measurements were taken six years after planting for E. cloeziana and three years for E. saligna. The study aimed to assess genetic parameters and select individuals at typical breeding evaluation ages in Brazil. Both methods demonstrated strong alignment, with high correlations in genetic parameters and values at both progeny and individual levels. Correlations exceeded 97% for progenies and 81% for individuals when analyzing the genetic values of diameter at breast height and height. The methods aligned closely under lower selection intensities but diverged under higher selection intensities. While the accuracy of LiDAR can be improved through refinement, the choice between these methods ultimately depends on operational factors such as the availability of skilled labor and equipment.
Keywords: E. saligna; Eucalyptus cloeziana; Forestry evaluation techniques; growth phenotyping; selection intensity